2022
DOI: 10.1186/s12886-022-02592-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiological responses of astrocytes in optic nerve head due to biaxial stretch

Abstract: Background Elevated intraocular pressure (IOP) is the main risk factor for glaucoma, which might cause the activation of astrocytes in optic nerve head. To determine the effect of mechanical stretch on the astrocytes, we investigated the changes in cell phenotype, proteins of interest and signaling pathways under biaxial stretch. Method The cultured astrocytes in rat optic nerve head were stretched biaxially by 10 and 17% for 24 h, respectively. Then, we detected the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…NF-κB then translocates to the nucleus and induces the transcription of inflammation-related genes 32 . In addition, NF-κB activation is also regulated by the upstream MAPK family, including JNK, ERK, and p38MAPK 33 . MAPKs rapidly achieve signal transmission by converting from the non-phosphorylated to the phosphorylated state, which in turn promotes the phosphorylation of downstream substrates 34 .…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB then translocates to the nucleus and induces the transcription of inflammation-related genes 32 . In addition, NF-κB activation is also regulated by the upstream MAPK family, including JNK, ERK, and p38MAPK 33 . MAPKs rapidly achieve signal transmission by converting from the non-phosphorylated to the phosphorylated state, which in turn promotes the phosphorylation of downstream substrates 34 .…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the rearrangement of the cytoskeleton of astrocytes was able to generate traction forces on the substrate from within the cell, using integrins as mediators. Likewise, Li et al (Li et al, 2022) applied biaxial stretch to primary rodent astrocytes and observed changes in protein expression and signalling pathways that might be associated with astrocyte activation (Figure 7). Furthermore, the uniaxial strain was found to modulate the mechanical properties and behaviour of hiPSC-derived motor neurons.…”
Section: Mechanical Stressmentioning
confidence: 99%
“…It has been suggested that MAPK signaling pathways are involved in the onset or progression of glaucoma [108]. In a model simulating glaucoma conditions with biaxial stretching of optic nerve head astrocytes, bioinformatic and enrichment analysis identified the MAPK pathway, among others, to be of potential interest in cellular responses after mechanical stimulation [109]. With TGF-β stimulation, a factor known to be implicated in primary open angle glaucoma [110], human trabecular meshwork cells (TMCs) were transcriptomically analyzed and the MAPK cascade was found to be significantly enriched within the differentially expressed genes [111].…”
Section: Mapk In the Retinamentioning
confidence: 99%